Technology Transfer: An Efficient Means of Knowledge Flow - Szakály, Dezső (Theory, Methodology, Practice – Review of Business and Management, 2012)
The factor to what extent a country can join the more and more intensive international technology transfer is one that has a decisive impact on the development of the national economy. In the past few years it has been possible to observe two characteristic phenomena in the efforts of the countries undertaking dominant roles in the transfers completed for making the knowledge flow more intensive. One is the result of globalisation and company activities becoming more international, which can be shown in the steady growth of transfer traffic. The other is an effort manifested in the countries taking specific steps to balance their transfer balance and to ensure that it is in the black.